2013
DOI: 10.1016/j.parkreldis.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Motor and non-motor symptoms of 1453 patients with Parkinson's disease: Prevalence and risks

Abstract: Considering that very few studies have assessed numerous clinical symptoms in the same report, these data provide a useful reference for the clinical course of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 41 publications
2
69
3
6
Order By: Relevance
“…With respect to the first research question, we found a slightly lower frequency of motor complications in our patients than several other studies (approximately 20% of our study participants with either of the motor complications vs. more than 22% of motor fluctuations and more than 26% of dyskinesias in other studies) (Nicoletti et al., 2016; Yoritaka et al., 2013; Martínez‐Martín et al., 2014; Hashim et al., 2014; Larsen et al., 2000; Schrag & Quinn, 2000). It is possible that the somewhat lower frequency of motor complications was partly due to the profile of the study participants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With respect to the first research question, we found a slightly lower frequency of motor complications in our patients than several other studies (approximately 20% of our study participants with either of the motor complications vs. more than 22% of motor fluctuations and more than 26% of dyskinesias in other studies) (Nicoletti et al., 2016; Yoritaka et al., 2013; Martínez‐Martín et al., 2014; Hashim et al., 2014; Larsen et al., 2000; Schrag & Quinn, 2000). It is possible that the somewhat lower frequency of motor complications was partly due to the profile of the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…and 548 mg in the study by Yoritaka et al.) (Yoritaka et al., 2013; Hashim et al., 2014). As this study was part of an epidemiologic survey of PD, all patients in the region were enrolled, included early cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations